Isolation and identification of Aeromonas hydrophila from silver carp and its culture environment from Mymensingh region - Rashid, M Mamnur; Hossain, MS; Ali, MF (Journal of the Bangladesh Agricultural University, 2014)
The pathogenic bacteria, Aeromonas hydrophila from naturally infected silver carp, Hypophthalmichthys molitrix were isolated and identified from a fish farm in Mymensingh. Fish showed motile Aeromonas septicemia (MAS) like reddish head and anal region, pale body colour and external haemorrhages. Intestine, liver, kidney and environmental samples such as sediment, feed and water were inoculated onto the Aeromonas isolation medium (AIM) and TSA plates. The AIM colonies were undergone specific characterization for Aeromonas hydrophila. Quantitative studies of bacterial flora of fish on TSA plates showed that the total bacterial load in intestine, liver and kidney of the sampled fish, sediment, feed and water of the environment were 1.00 × 105 to 1.50 × 105 CFU/g, 2.7 × 102 to 4.46 × 104 CFU/g, 1.00 × 103 to 2.17 × 103 CFU/g, 1.90 × 104 CFU/g, 4.10 × 103 CFU/g and 2.50 × 103 CFU/ml, respectively. After isolation, A. hydrophila was finally identified by their specific morphological, physiological and biochemical characteristics. They were gram negative, rod shaped, motile bacteria that showed positive reaction for oxidase and catalase, fermented glucose and were resistant to vibriostatic agent 0/129. They showed positive result in esculin hydrolysis test. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19943 J. Bangladesh Agril. Univ. 11(2): 373-376, 2013